Implementasi Activity Base Costing Dalam Pengendalian Biaya Pada CV. Berlian Kilau Abadi-Breakshoot Billiar - Nurmailiza Nurmailiza; Yuli Yusnita (Jurnal Adminitrasi Bisnis Nusantara, 2023)
This study aims to describe the determination of the cost of production that has existed so far in the company CV Berlian Kilau Abadi-Breakshoot Billiard. Furthermore, calculating the production costs using the Activity-Based Costing approach. This study uses a qualitative approach with the case method. This study obtained data from the company in the form of secondary data, and primary data in the form of direct interviews with research informants. Research data through the data credibility testing process. Data were analyzed using the approach of Miles and Huberman (1994), which was carried out simultaneously with the process of data collection, data presentation, data reduction, and drawing conclusions or verification. The research results show that the company has never done a detailed calculation of production costs, only they are exploring the amount of costs that are likely to be incurred before determining the selling price. The selling price set for the billiard table rental game / sports service is primarily based on the price prevailing in the Bengkulu City market. The company has not detailed the types of costs incurred and how much they cost in determining the existing rental rates. The bookkeeping and financial management system still uses the traditional system by recording all the receipts and expenses that have occurred, and at the end of the month the total will be calculated to see if it gets a profit or a loss. The calculation of production costs using the Activity-Based Costing (ABC) approach is carried out in order to obtain the total production costs for each available hour. There are 19 cost items and their triggers which are identified as components of production costs. Costs are separated into direct and indirect production costs, then calculated the amount of the cost of production per hour of billiard table rental services. The total production costs generated are still below the selling price, namely IDR 17,638.09 (direct production costs IDR 15,691.88, and indirect costs IDR 1,946.21). Judging by the selling price of IDR 25,000, it can be concluded that the company is still in the profit category.